Dampak ASEAN-China free trade agreement (ACFTA) terhadap pertumbuhan ekonomi Indonesia - Azza Ayullah Kusuma (Jurnal Ekonomi Pembangunan, 2017)
The purpose of this study investigates the impact of ACFTA, Indonesian trade, the exchange rate on economic growth in Indonesia. The data used secondary data during 1997-2016 were sourced from UNCOMTRADE, ASEAN Statistics, and World Bank. The method used is a quantitative approach with vector error correction model (VECM). The findings of this study in the long run show that Indonesian trade, ACFTA has a positive and significant effect on economic growth, while the rupiah exchange rate variable has a negative and significant effect on economic growth